Conservation Potential of Abandoned Military Areas Matches That of Established Reserves: Plants and Butterflies in the Czech Republic - Cizek, Oldrich; Vrba, Pavel; Benes, Jiri; Hrazsky, Zaboj; Koptik, Jiri; Kucera, Tomas; Marhoul, Pavel; Zamecnik, Jaroslav; Konvicka, Martin (PloS one, 2013)
Military training generates frequent and irregular disturbance followed by succession, resulting in fine-scaled mosaics of ecological conditions in military training areas (MTAs). The awareness that MTAs may represent important biodiversity sanctuaries is increasing recently. Concurrently, changes in military doctrine are leading to abandonment of many MTAs, which are being brought under civilian administration and opened for development. We surveyed vascular plants in 43 and butterflies in 41 MTAs in the Czech Republic and compared the records with plants and butterfly records from 301 and 125 nature reserves, respectively. After controlling for effects of area, geography, and climate, we found that plant species richness was equal in the two land use categories; butterfly richness was higher in MTAs; reserves hosted more endangered plants and more endangered butterflies. Ordination analyses, again controlled for potential nuisance effects, showed that MTAs and reserves differed also in species composition. While specialist species of nationally rarest habitat types inclined towards the reserves, MTAs hosted a high representation of endangered species depending on either disturbed ground, or successionaly transient conditions. These patterns reflect the history of the national nature reserves network, and the disturbance-succession dynamics within MTAs. The conservation value of formerly army-used lands is increasingly threatened by abandonment, and conservationists should support either alternative uses mimicking army activities, or sustainable management regimes.